Strategi Guru Dalam Membimbing Belajar Siswa Broken Home di SDN 07 Kubang Putih - Aziizirrahman, Abdul (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2023)
This study aims to determine how the condition of children from broken-home families. To find out the impact of Broken Home families on the learning activities of SD N 07 Kubang Putiah students, Agam, West Sumatra. This type of research is a type of qualitative research. The data collection methods used are observation and interview. The subject of this research is a sixth-grade student with a Broken Home family background. Broken Home in this study focuses on children who experience problems in learningactivities at school as a result of their parent's divorce. The results showed that the student's learning activities improved due to special guidance from teachers at school.